Pyrolysis oil from post-consumer packaging and its ageing: Physical and chemical properties and drop-in performance in a power generating unit - Gian Claudio Faussone; Tine Seljak; Edita Jasiukaitytė-Grojzdek; Urban Žvar Baškovič; Tomaž Katrašnik; Miha Grilc (Energy Reports, 2023)
Waste plastics/pyrolysis oil (WPO) obtained from a batch rotary kiln pyrolysis reactor was collected and stored for 60 months in dark at 10 °C, periodically thoroughly characterized for changes in physical and chemical properties and finally tested as the drop-in fuel for power generating units. Changes during storage were manifested through chain length increase from C5-C33 to C5-C43 and distillation curve shift for 150 °C. The changes were attributed to repolymerization reactions and consequently lowered alkene to alkane ratio, occurring at a slow rate during storage. The drop-in performance of aged WPO was evaluated under a wide range of operating parameters in a compression ignition engine based power generating unit. The results were compared with those obtained with conventional diesel fuel at the same injection and gas path parameters. Emission wise, the trends obtained for aged WPO and diesel were differing in the range of 20%, while more than 50% lower CO emissions could be obtained with WPO in optimized operating points, albeit the order of magnitude higher viscosity of aged WPO. With tailored control strategies and careful guidance of in-cylinder thermodynamic conditions it is possible to exploit the increased alkane content of aged WPO. Results provide a comprehensive basis for further development of control strategies, oriented towards stationary power generation applications with high intermittency, where long and mid-term storage of WPO is expected.